Stressors during the prodromal phase of major depressive episode (CHR-D) - Meisenzahl, Eva; Schultze-Lutter, Frauke; Stegmüller, Veronika; Schulte-Körne, Gerd; Greimel, Ellen; Klingele, Cosima; Dannlowski, Udo; Hahn, Tim; Romer, Georg; Romanos, Marcel; Deserno, Lorenz; Theisen, Christian; et al. (Frontiers in Psychiatry, 2024)
Introduction Early recognition and indicated prevention is a promising approach to decrease the incidence of Major depressive episodes (MDE), targeting the patients during their clinical high-risk state of MDE (CHR-D). The identification of a set of stressors at the CHR-D increases the success of indicated prevention with personalized early interventions. The study evaluated stressors in the early phase of depression, developed on the basis of a patient survey on stressors. Methods Sixty-eight inpatients (ICD10: F3x.xx) with a reported high risk state for major depressive episode (CHR-D) were included in the current study. Stressors during CHR-D were retrospectively explored using a semi-structured clinical interview supplemented by open-ended questions. A qualitative explorative content analysis was provided to identify a pattern of stressors during the prodromal phase of the patients, based on the patient’s perspective. A frequency analysis was performed for the evaluation of the prevalence of reported source of stress. Results All patients reported stressors in the prodromal phase of depression. Results demonstrates that patients with depressive disorder typically report multiple stressors, with the most common number being four. First, 18 stressors-groups were identified during coding. Interpersonal conflicts and disappointments in close relationships were most frequently reported stressors during the prodromal phase at 44.1%. The second most frequent stressor mentioned was the high qualitative or quantitative demands at work (38.2%). The third frequent source of stress was changes in close relationships and in family relationships (33.8%). Based on the categories of stressors described in the patient survey during the prodromal phase we suggested a model of stressors in CHR-D during the prodromal phase of the MDE. Discussion The identification of a set of stressors at the early stage of MDE may increase opportunities for early intervention. In everyday clinical practice, preventive psychiatry needs clinical and adapted instruments for recording stressors in today’s society. This knowledge is necessary in order to develop precisely indicated prevention for depressive disorders.